2021
DOI: 10.1002/hed.26692
|View full text |Cite
|
Sign up to set email alerts
|

Circulating hybrid cells predict presence of occult nodal metastases in oral cavity carcinoma

Abstract: Background Levels of circulating hybrid cells (CHCs), a newly identified circulating tumor cell (CTC), correlate with disease stage and progression in cancer. We investigated their utility to risk‐stratify patients with clinically N0 (cN0) oral cavity squamous cell carcinoma (OCSCC), and to identify patients with occult cervical lymph node metastases (pN+). Methods We analyzed peripheral blood samples for CHCs with co‐expression of cytokeratin (tumor) and CD45 (leukocyte) from 22 patients with cN0 OCSCC using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Similarly, monitoring the population of triple negative circulating cells in a patient with ER + or HER2 + breast cancer in targeted therapy may allow early identification of the emerging resistant disease. Additionally, for CHCs it is yet to be determined whether they are direct effectors of metastatic risk; however, longitudinal monitoring of CHCs or other circulating effector cell populations may have clinical utility in predicting the metastatic risk at diagnosis and after curative-intent procedures or therapeutics [ 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, monitoring the population of triple negative circulating cells in a patient with ER + or HER2 + breast cancer in targeted therapy may allow early identification of the emerging resistant disease. Additionally, for CHCs it is yet to be determined whether they are direct effectors of metastatic risk; however, longitudinal monitoring of CHCs or other circulating effector cell populations may have clinical utility in predicting the metastatic risk at diagnosis and after curative-intent procedures or therapeutics [ 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…While cell fusion occurs in both homeostatic and noncancerous inflammatory states [ 91 , 92 , 93 ], it has recently been described in malignancy [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Heterotypic cell fusion hybrids are generated in cell co-culture [ 29 ], in vitro murine models of injury-regeneration [ 94 , 96 ], in tumorigenesis [ 29 , 103 ], and in human cancer patients [ 29 , 33 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. Much like the sampling of a tumor’s genome and proteome by CAMLs, tumor-immune hybrid cells harbor immune and neoplastic cell attributes, and thus provide important information with regard to tumor state and the tumor microenvironment.…”
Section: Tumor Cell Fusion Tumor-immune Hybrids and Circulating Hybri...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was established in different studies of the patients with various gastrointestinal cancers [ 80 , 82 ] that there was a decrease in the levels of hybrids in blood after chemotherapy. Increase of the CHCs concentration in blood of the patients with oral carcinomas allowed Henn et al (2021) predicting the emergence of hidden metastases in lymph nodes, thus providing an opportunity to avoid the highly invasive neck dissection, which leads to complications in 25% of the cases [ 81 ].…”
Section: Characteristic Of Hybrid Cancer Cellsmentioning
confidence: 99%
“…A recent study has demonstrated the so-called circulating hybrid cells (CHCs) in oral cavity squamous cell carcinoma [ 76 ], which consist of lineages that mix the profile of neoplastic cells with macrophages, expressing EPCAM and/or CKs, in addition to leukocyte-determining proteins, such as CD45. Interestingly, high levels of CHCs were correlated with the occult nodal metastases presence, but in contradiction, they were not correlated with the tumor stage [ 76 ]. Therefore, CTCs in HNSCC follow a traditional expression pattern of epithelial biomarkers, such as CKs.…”
Section: Ctcs In Hnsccmentioning
confidence: 99%